2013
DOI: 10.1371/journal.pone.0081519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha Linolenic Acid Supplementation on Serum Prostate Specific Antigen (PSA): Results from the Alpha Omega Trial

Abstract: BackgroundAlpha linolenic acid (ALA) is the major omega-3 fatty acid in the diet. Evidence on health effects of ALA is not conclusive, but some observational studies found an increased risk of prostate cancer with higher intake of ALA. We examined the effect of ALA supplementation on serum concentrations of prostate-specific antigen (PSA), a biomarker for prostate cancer.MethodsThe Alpha Omega Trial (ClinicalTrials.gov Identifier: NCT00127452) was a double-blind, placebo-controlled trial of ALA and the fish fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Similarly, a cross-over, 6-month lower-dose walnut supplementation (35 g/d) with a 4-week washout interval, failed to reduce PSA among middle-aged men [ 199 ]. Similarly, the Alpha Omega trial [ 200 ] failed to demonstrate differences in the PSA concentrations of older adults with a history of myocardial infarction following 40 months of margarine spread-based α-linolenic acid (ALA) supplementation compared with placebo. When men were randomized to receiving EPA (2.4 g/d) for 12 weeks, or no intervention in the “Study of EPA Effects on Prostate Cancer” (SEEPC) [ 201 ], no differences in PSA response were recorded.…”
Section: Fatty Acids (Fa) and Foods Rich In Fatty Acidsmentioning
confidence: 99%
“…Similarly, a cross-over, 6-month lower-dose walnut supplementation (35 g/d) with a 4-week washout interval, failed to reduce PSA among middle-aged men [ 199 ]. Similarly, the Alpha Omega trial [ 200 ] failed to demonstrate differences in the PSA concentrations of older adults with a history of myocardial infarction following 40 months of margarine spread-based α-linolenic acid (ALA) supplementation compared with placebo. When men were randomized to receiving EPA (2.4 g/d) for 12 weeks, or no intervention in the “Study of EPA Effects on Prostate Cancer” (SEEPC) [ 201 ], no differences in PSA response were recorded.…”
Section: Fatty Acids (Fa) and Foods Rich In Fatty Acidsmentioning
confidence: 99%
“…Forty-nine trials, including 24,272 randomised participants, met the inclusion criteria. Trials ranged in size from 36 randomised participants (Rossing 1996) to 4997 randomised participants (PREDIMED 2013), with 15 trials randomising at least 250 participants (AlphaOmega -ALA;Bates 1989;DART fat 1989;EPIC-1 2008;EPIC-2 2008;EPOCH 2011;FAAT -Leaf 2005;MRC 1968;NDHS Open 1st 1968;ORL 2013;PREDIMED 2013;Sydney Diet-Heart 1978;Veterans Admin 1969;WAHA -Ros 2016;WINS 2006).…”
Section: Included Studiesmentioning
confidence: 99%
“…Despite the promise of omega-3 fatty acids, not all studies agree. Supplementing 2 g alpha-linolenic acid (ALA) per day for 40 months in 1,622 men with PSA <4 ng/ml did not change their PSA [ 72 ]. However, another study found that a high blood serum n-3 PUFA and docosapentaenoic acid (DPA) was associated with reduced total PCa risk while high serum EPA and docosahexaenoic acid (DHA) was possibly associated with increased high-grade PCa risk [ 73 ].…”
Section: Nutrientsmentioning
confidence: 99%